2001
DOI: 10.1046/j.0007-1323.2001.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial assessing anal sphincter injuries after stapled haemorrhoidectomy

Abstract: The large circular anal dilator used for stapled haemorrhoidectomy increased the risk of anal sphincter injuries, which may become problematic with ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 21 publications
0
69
1
6
Order By: Relevance
“…In a number of cases, blood transfusion was needed in order to restore hemoglobin levels. 3,8,23,49,50 The incidence of early bleeding was greatly reduced following the introduction of the second wave of stapling instruments (PPH01 to PPH03). The introduction of this new instrument resulted in a smaller staple width, which also reduced the necessity for oversewing of the staple line.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of cases, blood transfusion was needed in order to restore hemoglobin levels. 3,8,23,49,50 The incidence of early bleeding was greatly reduced following the introduction of the second wave of stapling instruments (PPH01 to PPH03). The introduction of this new instrument resulted in a smaller staple width, which also reduced the necessity for oversewing of the staple line.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized trials comparing stapler haemorrhoidopexy with conventional haemorrhoidectomy were conducted to test the feasibility and efficacy of the technique (3,7,8,9,10,12).…”
Section: Discussionmentioning
confidence: 99%
“…it represent radical change in the treatment of haemorrhoids by avoiding multiple excisions and suture lines in sensitive perianal area and thus offer less postoperative pain than with conventional technique. Several randomized controlled trials (7,8,9,10,11,12) assessed results of stapler haemorrhoidopexy. Results of These studies have consistently shown a decrease in postoperative pain, analgesic requirement, length of surgical procedure, shorter hospital stay and early return to daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, postoperative incontinence after stapled hemorrhoidectomy was reported in up to 28 % of cases [61]. In most patients, incontinence is transitory, due to excessive anal stretching secondary to circular anal dilator insertion [62]. At long-term follow-up, persistent continence problems were reported in a minority of patients with no significant difference with respect to conventional hemorrhoidectomy [61,[63][64][65].…”
Section: Complicationsmentioning
confidence: 99%